(untitled) (Jurnal Destinasi Pariwisata, 2025)
Pasar Gede in Surakarta City is a traditional market that has evolved into a culinary tourism destination, offering a rich variety of traditional foods and beverages. Despite its cultural significance, the market faces challenges such as negative visitor reviews, limited parking space, and underutilized digital promotion. This study aims to analyze the existing marketing mix (7P), assess external environmental factors using the PEST-C framework, and formulate appropriate marketing strategies through SWOT analysis. The research employs a qualitative descriptive method with purposive sampling, involving interviews with vendors and visitors, field observations, and document analysis. Findings reveal strengths in product authenticity and strategic location, but weaknesses in promotion and physical infrastructure. External opportunities include rising interest in cultural tourism and government support, while threats stem from competition with modern culinary venues and poor online reputation. The study proposes strategies such as community-based digital promotion, service quality improvement, and collaborative revitalization efforts to enhance Pasar Gede’s competitiveness as a culinary tourism destination.